PANDANGAN PEMUKA AGAMA TENTANG URGENSI PENGATURAN HUBUNGAN UMAT BERAGAMA DI PROVINSI BALI - Ahsanul Khalikin (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
This study employs qualitative approach and some instruments to collect the data such as interview, Focus Group Discussion (FGD), literature study, and document analysis. The purposes of the study are to gather the information from the religious leaders about urgency in managing the adherent relationship, to know the management form, and to find out the aspects that are managed. The result of study concludes that religious leaders really agree to the regulation determined by government on urgency in managing the adherent relationship and involve the religious leaders as well community organization to build interfaith harmony.